SPATIO-TEMPORAL ANALYSIS OF SHIFTS IN THE COMPOSITION OF FACTORS CAUSING DIVORCE CASES IN SULAWESI, INDONESIA - Nur Hikmah Auliana; Muspita Sari; Arham Nur Alim (Institut Agama Islam Negeri Bone, 2026)
Changes in the composition of divorce causes are important to understand because they reflect evolving social dynamics. However, previous studies have mainly focused on the number of divorce cases or dominant causes, while changes in the composition of divorce causes over time and across regions remain underexplored. This study analyzes spatio-temporal changes in the composition of divorce causes across Sulawesi, Indonesia, during 2023–2025. A descriptive quantitative approach was employed using secondary data from the Indonesian Central Statistics Agency on divorce cases by province and their causes. The analysis combined composition percentages, proportion changes, and Total Variation Distance (TVD). Results showed that continuous disputes and quarrels were the leading cause of divorce in all provinces throughout the study period. Proportion change analysis indicated that this factor generally increased, whereas economic problems, domestic violence, and abandonment by one party tended to decline in several provinces. TVD analysis revealed spatial variation in compositional shifts. West Sulawesi experienced the largest changes (TVD = 0.1611 for 2024–2025; TVD = 0.1345 for 2023–2025), whereas Southeast Sulawesi showed the lowest TVD (0.0134), indicating the most stable composition of divorce causes.